Posterior Epidural Migration of a Lumbar Intervertebral Disc Fragment Resembling a Spinal Tumor: A Case Report - Kim, Hyojun (Ann Rehabil Med, 2018)
Posterior epidural migration of a lumbar intervertebral disc fragment (PEMLIF) is uncommon because of anatomical barriers. It is difficult to diagnose PEMLIF definitively because of its relatively rare incidence and the ambiguity of radiological findings resembling spinal tumors. This case report describes a 76-year-old man with sudden-onset weakness and pain in both legs. Electromyography revealed bilateral lumbosacral polyradiculopathy with a mass-like lesion in L2-3 dorsal epidural space on lumbosacral magnetic resonance imaging (MRI). The lesion showed peripheral rim enhancement on T1-weighted MRI with gadolinium administration. The patient underwent decompressive L2-3 central laminectomy, to remove the mass-like lesion. The excised lesion was confirmed as an intervertebral disc. The possibility of PEMLIF should be considered when rim enhancement is observed in the epidural space on MRI scans and electrodiagnostic features of polyradiculopathy with sudden symptoms of cauda equina syndrome.